Tradition and transmission: Shifting epistemological and (art-)historical grounds of contemporary art's relation to the past. (1st September 2019) - Hopfener, Birgit
AbstractThis article takes artworks by Ai Weiwei that engage with traditions, art historical, art critical and curatorial receptions of these works, and (art-)historical discourses on the 'critical problem of tradition' as the starting point to re-consider contemporary art's relationship with tradition. It adopts a critical global art historical perspective decentring universalized modern western frameworks and uncovering how contemporary art's relation to the past in today's spatially and temporally disjunctive global world has to be read from multiple and transculturally entangled historical, epistemological and geo-cultural perspectives.